RETENSI KARYAWAN DITINJAU DARI PENGHARGAAN, PENGEMBANGAN KARIR DAN PENILAIAN KINERJA KARYAWAN PADA PT MOMENTUM ANUGRAH INDONESIA DI KOTA BATAM - Feliks Dabur (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to analyze the positive and significant influence of appreciation, development, and performance appraisal on employee retention at PT Momentum Anugrah Indonesia. This research was conducted using quantitative research methods with a total of 70 respondents and data collection using a questionnaire. The results of this study found that: For the award variable tcount 1.004 > ttable 0.2352 with a significant level of 0.319 > 0.05. Therefore it can be concluded that H0 is accepted and Ha is rejected. This means that the reward variable does not partially affect the dependent variable. In the career development variable tcount 4.829 > ttable 0.2352 with a significant level of 0.000 < 0.05, it can be concluded that H0 is rejected and Ha is accepted. This means that the development independent variable partially affects the dependent variable. Performance appraisal variable tcount 0.736 > ttable 0.2352 with a significant level of 0.465 > 0.05 then it is concluded that H0 is accepted and Ha is rejected, meaning that the performance appraisal variable does not partially affect the dependent variable. The calculated F value for the independent variables X1, X2, and X3 is 41,728 with a significant level of 0.000. This significant value is less than 0.05. So it can be concluded that H0 is rejected and Ha is accepted. This means that the independent variables together have a positive and significant influence on the dependent variable